2020
DOI: 10.1016/j.idm.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the outbreak of COVID-19 in Japan by SIQR model

Abstract: The SIQR model is exploited to analyze the outbreak of COVID-19 in Japan where the number of the daily confirmed new cases is explicitly treated as an observable. It is assumed that the society consists of four compartments; susceptible individuals (S), infected individuals at large (I), quarantined patients (Q) and recovered individuals (R), and the time evolution of the pandemic is described by a set of ordinary differential equations. It is shown that the quarantine rate can be determined from the time depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 13 publications
0
59
0
3
Order By: Relevance
“…Since the waiting time distribution function can be assumed to be a well behaved function with a single peak 10 , 11 , the convolution can be evaluated by the saddle-point method of integration and it is given by 8 where is a characteristic time representing the peak position of and . Therefore, in the time period where does not depend on , I can show that …”
Section: Analysis Of the Infection Curve In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the waiting time distribution function can be assumed to be a well behaved function with a single peak 10 , 11 , the convolution can be evaluated by the saddle-point method of integration and it is given by 8 where is a characteristic time representing the peak position of and . Therefore, in the time period where does not depend on , I can show that …”
Section: Analysis Of the Infection Curve In Japanmentioning
confidence: 99%
“…The first wave of the outbreak of COVID-19 in various countries has been analyzed on the basis of Eq. ( 11 ), where is approximated by a piece-wise simple exponential function 8 , 9 , 12 – 16 .…”
Section: Analysis Of the Infection Curve In Japanmentioning
confidence: 99%
“…We adopt a SIQR model to represent the four compartments characteristic of the COVID-19 pandemic: Susceptible ( S ), Infected ( I ), Quarantined ( Q ) and Recovered ( R ), recently, directly applied to tackle COVID-19 propagation in other studies (Italy 44 and Japan 45 ). Following the argumentation of Pedersen and Meneghini 44 we do not explicitly designate the E state, given the evidence suggesting that the COVID-19 virus can be propagated without first exhibiting visual symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…(1). It is known [2] that ¡É´Øµ is given by a convolution of the incubation period (from infection to tested positive) distribution function and the number of infecteds. Furthermore, since the incubation period distribution is a well behaved function with a single peak [4,5], it is shown that ¡É´Øµ » Á´Ø µ (5) holds.…”
Section: Methods For Fitting the Infection Curve Siqr Modelmentioning
confidence: 99%